Pemilihan Supplier Bahan Baku Biji Plastik Menggunakan Metode Weighted Product (WP) - Pratama, Mohamat Rizki; Jumali, Muhamad Abdul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Industrial competition in Indonesia is getting tougher. One industry competition that continues to grow is the plastic furniture industry. Household furniture made of plastic has many advantages, namely durability and a variety of colors. The selection of quality raw materials by a company has a significant influence on the products it produces. Good raw material management is expected to enable the company to carry out the entire production process well and be able to compete with other companies. The purpose of this study is to select the best supplier in a plastic furniture company in Surabaya. Data collection was conducted at a plastic furniture company in Surabaya, by considering several criteria, namely production fulfillment, quality, price, service, and location. The method used in solving this problem is the Weighted Product method. Weighted Product method is one of the methods in the decision support system. The results of the calculation of supplier selection using the weighted product method, the best alternative supplier is Supplier D, because it has the highest V value of 0.408. The second highest value is for Supplier C got a value of 0.316, the lowest value of the three suppliers is Supplier B with a value of 0.277.